Implementación de un servidor de video streaming basado en los sistemas de gestión de aprendizaje LMS. - Loján Calle, Viviana del Rocío (2017)
The present thesis research consists in the study of the implementation of a video streaming server for its deployment into a learning management system for the Electronic and Telecommunications Engineering career of the Energy Faculty of the National University of Loja to improve the learning process to ease the development of the activities for both teachers and students. It has been researched the study of the video codecs, their main characteristics, advantages and disadvantages, as well as their storage capacity and the most viable option to provide a good video quality, reducing the energy consumption in the devices. In addition, the necessary requirements for the implementation of an educational environment platform were also established. With all the above, we want to provide a video solution to improve learning within the higher education environment. For the development of the present work has divided the investigation in stages, the first one of study, followed by another one of comparison and the last is the selection of the codec and server of video streaming aligned to the needs of the career.